2012
DOI: 10.1111/j.1365-2869.2012.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive dopamine and hypocretin deficiencies in Parkinson’s disease: is there an impact on sleep and wakefulness?

Abstract: Summary Sleep–wake disturbances are frequent in patients with Parkinson’s disease, but prospective controlled electrophysiological studies of sleep in those patients are surprisingly sparse, and the pathophysiology of sleep–wake disturbances in Parkinson’s disease remains largely elusive. In particular, the impact of impaired dopaminergic and hypocretin (orexin) signalling on sleep and wakefulness in Parkinson’s disease is still unknown. We performed a prospective, controlled electrophysiological study in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 37 publications
(73 reference statements)
1
48
1
7
Order By: Relevance
“…This delineates the role of the hypocretin system in wake-sleep regulation and in NREM-REM regulation. Cerebrospinal hypocretin levels are often normal or subnormal but there are fewer hypocretinergic neurons in hypothalamus in PD (Wienecke et al, 2012). Surprisingly, one study found high a level of hypocretin-1 (orexin-A) (Bridoux et al, 2013), but the small number of patients limited further conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…This delineates the role of the hypocretin system in wake-sleep regulation and in NREM-REM regulation. Cerebrospinal hypocretin levels are often normal or subnormal but there are fewer hypocretinergic neurons in hypothalamus in PD (Wienecke et al, 2012). Surprisingly, one study found high a level of hypocretin-1 (orexin-A) (Bridoux et al, 2013), but the small number of patients limited further conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…First, sleep disturbances, such as excessive daytime sleepiness, nocturnal insomnia, and REM sleep behavior disorder (RBD), are common non-motor symptoms of PD, which are thought to arise from the progressive loss of oxerin-producing neurons in the hypothalamus [95][96][97]. Intranasal orexin may be able to normalize the sleep disturbances in PD.…”
Section: Orexinsmentioning
confidence: 98%
“…Second, the loss of dopaminergic transmission in Parkinson's disease not only affects the nigro-striatal projection but also dopaminergic circuits between basal ganglia and brainstem structures (particularly the pedunculopontine and laterodorsal tegmental nucleus), where important neurons of the arousal pathway and for the modulation of sleep stages are located [1,101,108]. Finally, mesocortical dopamine neurons innervate limbic areas (thalamus and hypothalamus) [1,101], where important regulators of sleep-wake cycle are located: a) the master circadian clock in the suprachiasmatic nuclei of the hypothalamus, which mainly involves coordinated expression and activation of various clock genes [109][110][111][112][113][114] and regulation of melatonin production [115], and b) orexin/hypocretin-containing neurons, important excitatory neuromodulators of sleep homeostasis [116], which interestingly seem to be progressively reduced over the course of Parkinson's disease [117].…”
Section: Sleep-wake Neurobiology In Prodromal Parkinson's Diseasementioning
confidence: 99%